The Effect of Leadership on Employee Performance Through Employee Motivation in Primary and Private Dental Clinics in Jakarta - Fitrani Rospita; Andreas Wahyu Gunawan (Journal of Social Research, 2023)
In the midst of today's new normal era, the world economy has become very competitive. Many companies are competing to create innovations and make modifications to produce the best service to be provided, especially in the health sector. Health services in the new normal era like today need adaptation in providing services to the community, especially at dental clinics. This study aims to test and analyze "The Influence of Leadership and Employee Motivation on Employee Performance" The sample used in this study was 150 respondents who worked at the Main and Private Dental Clinic Companies. Testing was carried out using SEM analysis. The results of this study support the hypothesis that Leadership has a positive influence on Employee Motivation, Employee Motivation has a positive effect on Employee Performance, Leadership has a positive influence on Employee Performance with Employee Motivation as a mediating variable. This research has implications for the owner and management of the Main Dental Clinic and Personal to improve Employee Performance by paying attention to and increasing Employee Motivation and Leadership, so that in the end it can affect Employee Performance.